Stochastic numerical analysis for static performance of composite laminates based on resampling method. (1st May 2023) - Lian, Yuhao; Wu, Fuqiang; Han, Yalin
Abstract: Due to the unstable properties of composite materials, it is of great significance to obtain the strength and its mechanical dispersion of composite laminates. The dispersion can be simply simulated using a recently developed Stochastic Numerical Analysis Architecture based on resampling method. This paper attempts to quantify the inconsistency of mechanical uncertainty between the composite mechanical test panels and the components by resampling method in two scales. Researchers have given different scale distribution prediction methods based on manufacturing and experiments for this phenomenon. By introducing resampling method and 3D random field into the Monte-Carlo simulation framework, a fast prediction method for structural uncertainty is established. Three sets of laminate strength experiment were done to verify the analysis architecture, and the results showed that the predicted strength and distribution are in good agreement with the experimental ones. Some intelligent algorithms regarding applications of the 3D random field are also addressed.